KAJIAN INFOGRAFIS MUSEUM NASIONAL INDONESIA - Sari Wulandari; Arif Priyono SA (Universitas Trisakti, 2018)
AbstractA Study of Infographic National Museum of Indonesia. Currently the National Museum of Indonesia (MNI) is revitalizing the museum towards the vision of “Museum of Indonesian Culture with International Level”. Through the exhibition “Be Indonesia”museum manager seeks to capture input from residents and experts. Various sourcesof information describing Indonesian culture are displayed, to convey the message tothe target audience through the information material in the form of graphic panels.Target communication of school students as a place to learn to understand the historyand local wisdom that make up the culture. Qualitative research methods by auditingvisualization of exhibit infographic materials on graphic panels, listing the conformitybetween the visual presented with the content or the content of the message, as wellas the context. Through this research is expected to be obtained a study on how theinfographical conditions presented on the show Exhibition Flow of MNI Story basedon DKV scholarship. The results of the research are recommendations aimed at MNImanagers in the form of panels graphic templates, is expected to be an input in preparingpermanent exhibition “Be Indonesia” for the new MNI. AbstrakKajian Infografis Museum Nasional Indonesia. Saat ini Museum NasionalIndonesia (MNI) sedang melakukan revitalisasi museum menuju ke arah visi “Museum Kebudayaan Indonesia Bertaraf Internasional”. Melalui Pameran “Jadilah Indonesia” pengelola museum berupaya menjaring masukan dari warga dan para ahli. Berbagai sumber informasi yang menggambarkan kebudayaan Indonesia ditampilkan, untuk menyampaikan pesan kepada target pemirsanya melalui materi informasi dalam bentuk panil-panil grafis. Target komunikasi siswa sekolah sebagai tempat belajar untuk memahami sejarah serta kearifan lokal yang membentuk kebudayaan. Metode penelitian kualitatif dengan cara mengaudit visualisasi materi infografis pameran padapanil grafis, mendata kesesuaian antara visual yang disajikan dengan konten atau isi pesan, serta konteksnya. Melalui penelitian ini diharapkan akan diperoleh kajian mengenai bagaimana kondisi infografis yang disajikan pada display Pameran Alur Kisah MNI berdasarkan keilmuan DKV. Hasil penelitian adalah rekomendasi ditujukan untuk pengelola MNI berupa template panil grafis, diharapkan dapat menjadi masukandalam mempersiapkan pameran tetap Alur Kisah untuk MNI yang baru.